(3cJGH aj GdYde hGdYed hGdUfYI GdEdgjIs
(3ChdgG (B:s
(3UaI GdQhM GdHGQO GdQWH hgh GdRjHb GdZQH heKGdg ceG JQi s
(3gcPG PcQ Ydi UaMI GdYfhGf OGNd MdjI edhfI s
(3hgh eLehYI ef Gdfbhd ai Yde GdUfYI GdEdgjI ef cJH eNJdaI JTJed Ydi cJGH GdCbGdje GdSHYI dCHi GdbGSe GdYQGbi jdjg eLehYI ef GdQSGFds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B143 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs